Fingerprint of tropical climate variability and sea level in sediments of the Cariaco Basin during the last glacial period. Issue 5 (19th February 2019) - Deplazes, Gaudenz; Meckler, Anna Nele; Peterson, Larry C.; Hamann, Yvonne; Aeschlimann, Beat; Günther, Detlef; Martínez‐García, Alfredo; Haug, Gerald H.
Abstract: High‐resolution palaeorecords of climate are critical to improving current understanding of climate variability, its sensitivity and impact on the environment in the past and in the future. Sediments from the Cariaco Basin off the coast of Venezuela have proven to be sensitive recorders of tropical palaeoclimate variability down to an annual scale. However, the fingerprint of climate and sea level in the sediments of the last glacial period is still not completely understood. In this study, lamination analysis of sediments from the Cariaco Basin is extended to the last glacial period. Detailed sedimentological and geochemical analysis (laser ablation–inductively coupled plasma–mass spectrometry) reveals couplets of light‐coloured, terrigenous‐rich and dark‐coloured, biogenic opal‐rich laminae, which are interpreted to reflect the seasonal migration of the Intertropical Convergence Zone. In addition, a previously undescribed, nearly pure terrigenous lamina type is observed, which is referred to hereafter as a 'C‐layer'. The C‐layers in the sedimentary sequence are interpreted as flood layers that originate from local rivers. The occurrence of these C‐layers is investigated for two core locations in the Cariaco Basin over the last 110 kyr by continuous X‐ray fluorescence scanning. Dansgaard–Oeschger oscillations are most clearly traced by proxies reflecting productivity and marine organic matter content of the sediment. In contrast, the abundance of terrigenous material differs at times between the two sites. On an interglacial to glacial timescale, the ability to record events causing C‐layers is likely to be influenced by changes in sea level and source proximity. On a millennial scale, both sediment cores contain more C‐layers during warmer interstadials compared with colder stadials during Marine Isotope Stage 3. This finding implies that interstadials were not only wetter than stadials, but probably also characterized by increased rainfall variability, leading to an enhanced frequency of flooding events in the hinterland of the Cariaco Basin.